The Integration Of Technology And Local Wisdom In The Economic Development Of Indonesian Society In The Era Of 5.0 - Ahmad Munir (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2025)
The Era 5.0 marks a paradigm shift in economic development that places humans at the center of innovation, with advanced technology as the primary driver. In the Indonesian context, the integration of technology and local wisdom serves as a crucial strategy for fostering sustainable and inclusive economic growth. This study aims to analyze how the application of digital technology can align with the values, practices, and traditional knowledge deeply rooted in society. The research employs literature review and qualitative methods to examine various successful integration models in the agriculture, tourism, and creative industry sectors. Data analysis was conducted through data condensation, data display, and conclusion drawing. The findings indicate that the integration of technology and local wisdom in the Era 5.0 is an essential strategy for building an advanced Indonesian economy while remaining rooted in cultural identity. Technology accelerates processes, enhances efficiency, and expands access to global markets, while local wisdom ensures sustainability and social cohesion. The synergy between the two has the potential to promote inclusive growth, reduce inequality, preserve cultural heritage, and create employment opportunities. Success, however, depends on equitable infrastructure development, digital literacy, intellectual property protection, and cross-sector collaboration, enabling Indonesia to become a global example of harmonizing tradition and innovation.          Abstrak Era 5.0 menandai pergeseran paradigma pembangunan ekonomi yang menempatkan manusia sebagai pusat inovasi, dengan teknologi canggih sebagai penggerak utama. Dalam konteks Indonesia, integrasi teknologi dan kearifan lokal menjadi strategi penting untuk menciptakan pertumbuhan ekonomi yang berkelanjutan dan inklusif. Penelitian ini bertujuan menganalisis bagaimana penerapan teknologi digital dapat berjalan selaras dengan nilai, praktik, dan pengetahuan tradisional yang telah mengakar di masyarakat. Metode yang digunakan adalah studi literatur dan metode kualitatif terhadap berbagai model integrasi yang berhasil di sektor pertanian, pariwisata, dan industri kreatif. Analisis data menggunakan kondensasi data, display data dan menarik Kesimpulan. Hasil penelitian ini menunjukkan bahwa Integrasi teknologi dan kearifan lokal di Era 5.0 menjadi strategi penting membangun ekonomi Indonesia yang maju sekaligus berakar pada budaya. Teknologi mendorong percepatan, efisiensi, dan akses pasar global, sementara kearifan lokal menjaga keberlanjutan dan kohesi sosial. Sinergi keduanya berpotensi menciptakan pertumbuhan inklusif, mengurangi kesenjangan, melestarikan budaya, dan membuka lapangan kerja. Keberhasilan bergantung pada pemerataan infrastruktur, literasi digital, perlindungan kekayaan intelektual, dan kolaborasi lintas sektor, sehingga Indonesia dapat menjadi teladan global dalam memadukan tradisi dan inovasi.